Cultured Endothelial Cells Regulate Platelet Adhesion to their Extracellular Matrix by Regulating its von Willebrand Factor Content - Wu, Ya-Ping; Sixma, Jan J; de Groot, Philip G (Thrombosis and Haemostasis, 1995)
Endothelial cells and their extracellular matrix formed in vitro are often used as a model for subendothelium in studies on platelet-vessel wall interaction. We have characterized the influence of culture conditions of endothelial cells on the formation of extracellular matrix and on the interaction of the matrix with platelets. Passage number, time of confluence, serum concentration and the addition of heparin, growth factors and antibiotics to the culture medium were varied and the extracellular matrices were isolated. The amount of fibronectin and von Willebrand factor present in the matrix were measured and the number of platelets adhering to these matrices after perfusion with citrated whole blood at a shear rate of 1000 s-l was determined. A three times increase of the amount of von Willebrand factor in the matrix was found when the serum concentration was increased from 2.5% to 30%. When the passage number of the cells was increased or the period during which the cells were at confluence was extended, the amount of von Willebrand factor in the matrix was decreased up to 50%. Addition of heparin or ECGS (endothelial cell growth supplement) decreased the von Willebrand factor content in the matrix. Addition of penicillin or streptomycin to the culture medium had no influence on the amount of von Willebrand factor deposited in the matrix or secreted into the medium, however, other antibiotics such as gentamycin and neomycin decrease the amount of von Willebrand factor in the matrix. No influence on the amount of fibronectin in the matrix was found under all conditions tested.There was a strong correlation between the amount of von Willebrand factor in the matrix and the number of platelets adhering to the matrix. A decrease or increase of the amount of von Willebrand factor was always correlated with a decrease or increase of the number of platelets adhering to the matrix. These results indicate that the synthesis and deposition of von Willebrand factor in the extracellular matrix by cultured endothelial cells is very sensitive to variations in culture conditions and that the amount of von Willebrand factor in the matrix predominantly determines the reactivity of the matrix for platelets.